Exploring the prevalence and risk factors of peripheral artery disease in patients with type 2 diabetes in sub-Saharan Africa: a systematic review and meta-analysis - Haile, Kirubel Eshetu; Amsalu, Atitegeb Alebachew; Kassie, Gizachew Ambaw; Asgedom, Yordanos Sisay; Azeze, Gedion Asnake; Gebrekidan, Amanuel Yosef (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundType 2 diabetes and lower-extremity peripheral artery disease (PAD) are growing global health problems associated with considerable cardiovascular and limb-related morbidity and mortality, poor quality of life, and high healthcare resource use and costs. Diabetes is a well-known risk factor for PAD, which further increases the risk of long-term complications. The primary aim of this systematic review was to ascertain the aggregated prevalence of PAD among individuals diagnosed with type 2 diabetes mellitus (T2DM) residing in sub-Saharan Africa.ObjectiveThe aim of this study was to determine the pooled prevalence and associated factors of PAD among patients with T2DM in sub-Saharan Africa.MethodsA systematic review and meta-analysis was performed in alignment with the guidelines established by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. To identify papers published in English up to 8 November 2024, the electronic databases of Medline, Web of Science, Science Direct, Excerpta Medica Database, Cochrane Library, African Journals Online, and Google Scholar were searched. A random-effects model was employed to estimate the pooled prevalence and associated factors of PAD.ResultsThis study revealed that the pooled prevalence of PAD among patients with T2DM was 35.7% [95% confidence interval (CI) 28.7, 42.7], reflecting the significant impact of DM on vascular health with statistically significant heterogeneity observed between studies (I2 = 94.9%, p < 0.001). Age, elevated low-density lipoprotein, elevated body mass index (BMI), and diabetes illness duration exceeding 10 years were the significant predictors.ConclusionThe aggregate burden of PAD in individuals with T2DM within the sub-Saharan African region is estimated at 35.7%, suggesting that a considerable segment of the sub-Saharan population has been impacted. Epidemiological studies utilizing precise assessment tools can enhance the early detection and prevention of PAD in T2DM and improve the certainty of findings.Clinical implicationThere is a need for integrated care approaches that prioritize the screening and management of PAD in individuals with T2DM. Given the high prevalence and associated complications, healthcare providers should implement routine PAD assessments in diabetes care protocols. Future research should focus on longitudinal studies that explore the causal relationships between risk factors and the development of PAD in patients with T2DM.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024611838.